2017
DOI: 10.1155/2017/7463571
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lemon Juice on Alcohol-Induced Liver Injury in Mice

Abstract: Chronic excessive alcohol consumption (more than 40–80 g/day for males and more than 20–40 g/day for females) could induce serious liver injury. In this study, effects of lemon juice on chronic alcohol-induced liver injury in mice were evaluated. The serum biochemical profiles and hepatic lipid peroxidation levels, triacylglycerol (TG) contents, antioxidant enzyme activities, and histopathological changes were examined for evaluating the hepatoprotective effects of lemon juice in mice. In addition, the in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
(40 reference statements)
2
24
0
3
Order By: Relevance
“…Many dietary natural products possess the abilities to protect against liver diseases [ 18 , 19 , 20 ]. They have shown the potential in improving the integrity of the gut mucosa, modulating the composition of the microbiota, reducing the toxic metabolites and translocated bacteria in the liver [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many dietary natural products possess the abilities to protect against liver diseases [ 18 , 19 , 20 ]. They have shown the potential in improving the integrity of the gut mucosa, modulating the composition of the microbiota, reducing the toxic metabolites and translocated bacteria in the liver [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…If the liver tissue is injured, liver cell swelling and necrosis, or increased membrane permeability of liver cells will occur, followed by secretion of transaminase into the blood, contributing to the increase in serum transaminase activity. Because aminotransferase activity in the liver is much higher than that in the blood under normal conditions, its change in serum is a specific marker used to assess hepatocellular damage in clinic (22,27). Zhang et al (3) investigated the protective effect of anthocyanins from purple sweet potato on acute carbon tetrachloride-induced liver injury in mice, which showed that the anthocyanins could significantly reduce the carbon tetrachloride-induced ALT and AST activity, demonstrating its protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some natural products have been found to protect against liver injuries [166][167][168][169][170]. Tea has also shown a beneficial effect on diet-and chemical-induced disorders in liver, including hepatic oxidative stress damage, inflammation, steatosis, and fibrosis [41,171,172].…”
Section: Hepato-protective Effectmentioning
confidence: 99%